Path Analysis on the Effects of Psychosocial Development, Nutritional Status, and Family Acceptance on Learning Achievement in Autistic Children, in Jember, East Java - Diana, Tutut Okta; Tamtomo, Didik; Murti, Bhisma (Journal of Maternal and Child Health, 2018)
Background: The prevalence of autism has been increasing worldwide annually. Autistic children are at higher risk of physical, mental, and intellectual disorders. However, autistic children may have above average academic achievement. With support from family, teacher, and society, autistic children can gain maximum academic achievement. This study aimed to determine the effects of psychosocial development, nutritional status, and family acceptance, on learning achievement in autistic children, in Jember, East Java.Subjects and Method: This was an analytic observational study with cross-sectional design. The study was conducted at Special Elementary School in Jember, East Java. A total sample of 50 autistic students were collected for this study by exhaustive sampling. The dependent variable was learning achievement. The independent variables were nutritional status, psychosocial development, and family acceptance. The data were collected by questionnaire and analyzed by path analysis.Results: Learning achievement was directly affected by psychosocial development (b= 0.36; SE= 0.13;p= 0.005) and nutritional status (b= 1.42; SE= 0.65; p= 0.029). Nutritional status was positively affected by strong family acceptance (b= 0.07; SE= 0.01; p<0.001).Conclusion: Learning achievement of autistic children is affected by psychosocial development and nutritional status.Keywords: learning achievement, psychosocial development, nutritional status, family acceptance, path analysisCorrespondence: Tutut Okta Diana. Masters Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami 36 A, Surakarta 57126, Indonesia. Email : tutut_od@yahoo.co.id. Mobile: +6281335466569.Journal of Maternal and Child Health (2018), 3(1): 59-67https://doi.org/10.26911/thejmch.201803.01.06